Pembinaan Disiplin Kerja Guru SD Negeri Cengklik II Surakarta - , SUTARTO, Dr. Markhamah, M. Hum, Dr. Ahmad Muhibbin, M.Si (2017)
The objectives of the research are to describe: 1) the teachers' discipline improvement program at SD Negeri Cengklik Surakarta; 2) the teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta; 3) results and follow up of the teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta, and 4) the supporting and inhibiting factors in teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta. The type of the research is a qualitative research. The design of the researh is ethnographical design. The research was undertaken at SD Negeri Cengklik Surakarta. The data collecting method is done using observation, indepth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The research concludes that: 1) the teachers' discipline improvement program at SD Negeri Cengklik Surakarta was settled based on need analysis. The teachers' discipline program are in the form of teachers' discipline improvement through direction, guidance, and development and supervision stimulus or motivation; 2) the teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta done in 4 (four) strategies, namely: a) the principal provide direction, b) the principal provide guidance, c) the principal provide development stimulus and suervision, and d) the principal provide reward; 3) results and follow up of the teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta effect the teachers' assessment and school achievement, and 4) the supporting factors in teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta cover motivation and support provided by the principal and teachers' enthusiasm to improve their self disciplin, and the principal's model. The inhibiting factors in teachers' discipline improvement program implementation at SD Negeri Cengklik Surakarta cover internal problems from the teachers themselves, namely teachers' laziness and possible personal matter experienced by the teachers.